The effectiveness of various insecticide active ingredients against the intensity of armyworm (Spodoptera exigua) attacks on onion plants (Allium ascalonicum L.) Varieties of Bima Brebes - Miftahunnaja, Muhamad; Suterajati, Arif; Ram Nugraha, Novendra; Deden, Deden; Dukat, Dukat (Pusat Publikasi Nusantara, 2023)
Shallots (Allium ascalonicum L.) are one of the leading commodities in agriculture. Shallots are commonly used as a seasoning for cooking, besides that shallots are also useful as traditional medicine because they have antiseptic substances contained in them. The productivity of onion plants often decreases as a result of pest attacks. Armyworm (Spodoptera exigua) is one of the obstacles in the cultivation of onion plants (Allium ascalonicum L.), high caterpillar attack rates can reduce onion productivity, even causing crop failure. One way to control this pest is to control by using insecticides with certain active ingredients. This study aims to determine the effectiveness of various insecticide active ingredients to control armyworm pests (Spodoptera exigua) on onion plants (Allium ascalonicum L.). The design in this study was a Group Randomized Design (RAK) with 4 treatments of insecticide active ingredients and controls, namely A (Profenofos), B (Emamectin benzoate), C (Metomil), D (Cipermethrin) and E (control). Each treatment was repeated 5 times so that there were 25 experimental units. The research was conducted in Gagasari Village, Gebang District, Cirebon Regency, West Java. The trial research time starts from June - September 2023. The results showed that the application of insecticides active ingredients Profenofos, Emamectin benzoate, Metomil and Sipermethrin did not cause phytotoxicity to onion plants. Insecticide, Profenofos has a relatively gentle attack and low when compared to other active ingredients. In general, it is seen that all active ingredients of insecticides tested are able to play a role in controlling pests well. Insecticide treatment has a significant effect on the yield of dry weight of shallots per plot when compared to treatment without insecticide control (control). Profenofos active ingredient insecticide treatment was seen to produce a higher dry tuber weight than other treatments even when compared to all insecticide active ingredients tested, reaching 24.92 kg or equivalent to 24.9 tons per hectare